2019
DOI: 10.1038/s42003-019-0589-x
|View full text |Cite
|
Sign up to set email alerts
|

Bright split red fluorescent proteins for the visualization of endogenous proteins and synapses

Abstract: Self-associating split fluorescent proteins (FPs) are split FPs whose two fragments spontaneously associate to form a functional FP. They have been widely used for labeling proteins, scaffolding protein assembly and detecting cell-cell contacts. Recently developments have expanded the palette of self-associating split FPs beyond the original split GFP1-10/11. However, these new ones have suffered from suboptimal fluorescence signal after complementation. Here, by investigating the complementation process, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 35 publications
0
64
0
Order By: Relevance
“…To improve the complementation efficiency of mNG2 1-10/11 , we performed directed evolution in an E. coli system using a strategy similar to our previous sfCherry3 work (4) and with more efficient cloning. In brief, mNG2 1-10 and mNG2 11 were expressed from a single mRNA with separate ribosome binding sites (RBS) ( Fig 1A), so that the two fragments have a relatively constant expression ratio across all E. coli colonies.…”
Section: Improving the Complementation Of Split Mng2 Using Directed Ementioning
confidence: 99%
See 2 more Smart Citations
“…To improve the complementation efficiency of mNG2 1-10/11 , we performed directed evolution in an E. coli system using a strategy similar to our previous sfCherry3 work (4) and with more efficient cloning. In brief, mNG2 1-10 and mNG2 11 were expressed from a single mRNA with separate ribosome binding sites (RBS) ( Fig 1A), so that the two fragments have a relatively constant expression ratio across all E. coli colonies.…”
Section: Improving the Complementation Of Split Mng2 Using Directed Ementioning
confidence: 99%
“…In the log-log plot, a linear fit to this relationship gave a slope of almost exactly 1 (0.99) (Fig 3A), validating the use of P2A site to produce proportional concentrations of mNG2 and TagBFP across the range of expression levels resulted from transient transfection. For the split FP 1-10/11 systems, on the other hand, it has been previously shown that the complementation process begins with a dynamic binding equilibrium between the two fragments (4,14). When the effective K D is much higher than the concentrations of co-transfected FP 1-10 and FP 11 fragments, this equilibrium cause the complemented FP signal to depend linearly on the expression reference with a slope of 2 on a log-log plot, while lowering the K D reduces this slope to 1 as the complementation becomes more efficient and approaches saturation (4).…”
Section: Engineering Of Clogfp Using Rational Design and Directed Evomentioning
confidence: 99%
See 1 more Smart Citation
“…Green and red asymmetrically-split fluorescent proteins have been used to combine cell and protein specificity in C. elegans neurons and synapses (Noma et al 2017;He et al 2019;Feng et al 2019); however, these strains used extrachromosomal arrays, not stable lines, which are more time-consuming to maintain and can have variable expression levels. To the best of our knowledge, there is only one available unbound FP1-10 stable C. elegans line, which expresses sfGFP1-10 in the germline (Hefel and Smolikove 2019), and there are no available lines with red FP1-10 fragments.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is only one available unbound FP1-10 stable C. elegans line, which expresses sfGFP1-10 in the germline (Hefel and Smolikove 2019), and there are no available lines with red FP1-10 fragments. Existing red split fluorophores are also much dimmer in C. elegans than green ones, despite recent improvements like split-sfCherry3 (Feng et al 2019).…”
Section: Introductionmentioning
confidence: 99%